Diffuse Idiopathic Skeletal Hyperostosis Coexisting with Ossification of Posterior Longitudinal Ligament Causing Dysphagia: A Case Report and Literature Review - Mirzashahi, Babak; Dehghani Firoozabadi, Mohammad Javad; Vahar, Mehdi; Forqan Khan, Yasin (Journal of orthopedic & spine trauma, 2018)
Diffuse idiopathic skeletal hyperostosis (DISH) is a systemic disease that is mostly reported in the spinal column with or without extraspinal involvement. DISH is often asymptomatic, but in case of progressive symptoms such as dysphagia, surgery may be required. Not only coexistence of DISH and ossification of posterior longitudinal ligament (OPLL) is uncommon, but also dysphagia as a presenting symptom in these patients is quite rare. To our knowledge, there are merely few such cases have been reported in the literature. In this study, we present the case of a 30-year-old man with the chief compliant of progressive dysphagia. After evaluation, diagnoses of DISH and OPLL were established, due to poor response to conservative treatment, the patient was managed surgically and favorable results were achieved.